2013
DOI: 10.3844/ajabssp.2013.230.238
|View full text |Cite
|
Sign up to set email alerts
|

Infuence of Seed Coating With Micronutrients on Growth and Yield of Winter Wheat in Southeastern Coastal Plains

Abstract: Polymer seed coating with micronutrients may provide important nutrients during plant growth and improve yields. The objective of this study was to determine the effect of three seed application rates (265, 395 and 530 mL 100 kg seeds-1) of polymer based mixture of Copper (Cu), Manganese (Mn) and Zinc (Zn) micronutrients on dryland winter wheat (Triticum aestivum L.) near Blackville, SC from 2010 to 2012. Compared to untreated control, seed coating significantly increased grain yields by 5.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…The increase in oil content with sulphur application might be due to the fact that sulphur helped in oil synthesis by enhancing the level of thioglucosides Dwivedi and Bapat, (1998) [6] . The results are in conformity with the findings of Tahir et al (2014) [24] these results are also in accordance with Pawel (2013) [20] in soybean.…”
Section: Protein Content (Per Cent)supporting
confidence: 93%
See 1 more Smart Citation
“…The increase in oil content with sulphur application might be due to the fact that sulphur helped in oil synthesis by enhancing the level of thioglucosides Dwivedi and Bapat, (1998) [6] . The results are in conformity with the findings of Tahir et al (2014) [24] these results are also in accordance with Pawel (2013) [20] in soybean.…”
Section: Protein Content (Per Cent)supporting
confidence: 93%
“…Which are the metallic components of one or more enzymes which are involved in various physiological functions, growth, development and crop productivity. These results are also in accordance with Pawel (2013) [20] in soybean, Barangule et al (2018) [4] in sorghum, Muhammad Imran (2015) [12] in maize.…”
Section: Grain Yield (Q Ha -1 )supporting
confidence: 89%
“…In that study, seed coating with N alone demonstrated greater efficacy than when combined with P, although coating with P enhanced P uptake by the plant. Similarly, Wiatrak (2013) demonstrated for wheat that seed coating with a mixed formulation of Cu, Zn and Mn (at 65, 395 and 530 ml kg −1 seed) significantly increased plant biomass and grain yield, as well as plant N and P contents. However, no effect of the seed coating treatment was observed in Cu, Mn and Zn contents.…”
Section: Seed Nutrient Content and Seed Coating With Nutrientsmentioning
confidence: 86%
“…Inocencio et al (2012 observed that Zn applications improved yields of soybeans, even when micronutrient availability in the soil was above the critical level. Wiatrak (2013) reported higher grain yields with application of polymer seed coating with micronutrients to winter wheat. According to Arshad et al (2011), grain yield of wheat increased with Cu and Zn application.…”
Section: Discussionmentioning
confidence: 99%